PERANCANGAN DESAIN INTERIOR GEDUNG STUDIO TV MENGGUNAKAN SOFTWARE BLENDER - Nova Nur Sakbani; Umi Hayati; Arif Rinaldi Dikananda (Universitas Mercu Buana, 2022)
Designing a studio can be done in many ways, including using blender software. The blender is an application that can be used for interactive images, including picture sharing and even 3D animation. Interior design USES principles such as nirvana, signage, color, drafting, and diagram shapes asa primary basis for understanding interior design. Interior design has become a primary 3D model for its original form. In the modeling technique used on blender software is a solid geometry modeling. These include ways of obtaining or creating data that illustrate objects, purpose models, complexity, proportion and usefulness, and ease the manipulation of models. In the original modelling, the surface is a sphere, cube, uv ball, ico ball, cylinder, cone, etc. 3D modeling requires designing being divided into several stages. For example, which object will be created asa base, how 3D objects are modeled, the lighting of objects and motion animation depends on the sequence of processes performed.